1996
DOI: 10.1073/pnas.93.11.5335
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Norwalk virus capsid protein in transgenic tobacco and potato and its oral immunogenicity in mice.

Abstract: (1) and expression of the capsid protein in recombinant baculovirus-infected insect cells (4) have facilitated the study of the virus and the development of a candidate vaccine (5). Expression of the Norwalk virus capsid protein (NVCP) in insect cells yields a protein with an apparent Mr of 58,000 that self-assembles into insect cell-derived Norwalk virus-like particles (i-rNVs) lacking viral RNA, which are reactive with sera from Norwalk virus-infected humans (4). Electron cryomicroscopy of i-rNV shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
293
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 519 publications
(311 citation statements)
references
References 23 publications
13
293
1
4
Order By: Relevance
“…Viral capsid proteins have previously been shown to be easily expressed in plants [12,13,34] and here we show that this is the case also for the RVFV N protein, as is evident from its expression at high concentrations. To the best of our knowledge, this is the first time RVFV antigen expression has been demonstrated in plants.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Viral capsid proteins have previously been shown to be easily expressed in plants [12,13,34] and here we show that this is the case also for the RVFV N protein, as is evident from its expression at high concentrations. To the best of our knowledge, this is the first time RVFV antigen expression has been demonstrated in plants.…”
Section: Discussionsupporting
confidence: 81%
“…It is therefore likely that the non-responders had lower intake, or none at all, compared with the responders. Others have previously shown that plant extracts delivered by gastric intubation [13] or pelleted plant material [15] are feasible alternatives to free feeding. These are delivery modes that would help to ensure that every mouse would consume equal amounts of plant material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Edible plant vaccines against enterotoxic Escherichia coli (ETEC; Refs. 14 & 15), cholera toxin [17,18], and norovirus [19,20] have already passed pre-clinical trials and preliminary human clinical trials show very promising results -transgenic plants can stimulate a two-way immune response, both systemically and mucosally. Improvement of administration protocols and the use of adjuvants during oral vaccination could then be important ways of further increasing efficacy of edible vaccines.…”
Section: Introductionmentioning
confidence: 99%